Pengaruh Retensi dan Konflik Kerja Terhadap Kinerja Karyawan di PT Lintang Mega Pertama : The Influence of Retention and Work Conflict on Employee Performance at PT Lintang Mega Pertama - Nayla Fariza Aulia; Henny Armaniah (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
PT Lintang Mega Pertama is a company engaged in construction services and relies heavily on employee performance in completing various projects. However, the company faces problems related to employee retention and work conflicts that can affect performance. This study aims to determine the effect of retention and work conflicts on employee performance. The study uses a quantitative approach with analytical methods that include validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination. Data were collected through interviews, distributing questionnaires to 47 respondents, and supplemented by documentation and literature studies. The results of the study indicate that retention has a positive and significant effect on employee performance of 2,322> t table of 1,680, so Ho is rejected and Ha is accepted. Work conflicts also have a significant effect on employee performance from the calculated t value of 2,622> t table of 1,680, so Ho is rejected and Ha is accepted. Simultaneously, retention and work conflict have a significant effect on employee performance at PT Lintang Mega Pertama, so Ho is rejected and Ha is accepted. The value of 12.123 > F table is 3.209. This study provides practical contributions for companies in formulating better retention and conflict management strategies to improve employee performance